A FDEM-based 2D coupled thermal-hydro-mechanical model for multiphysical simulation of rock fracturing - Yan, Chengzeng; Xie, Xin; Ren, Yuhang; Ke, Wenhui; Wang, Gang (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2022)
A coupled thermal-hydro-mechanical (THM) model based on the combined finite-discrete element method (FDEM) is presented for simulating rock cracking driven by multi-physics. The THM model contains three parts: a fracture-pore mixed seepage model, a heat transfer model, and a fracture mechanics calculation model. By combining any two of the above three models, a coupled thermal-mechanical (TM) model, a coupled hydrothermal (TH) model, and a coupled hydromechanical (HM) model are constructed. Then, the TM model, TH model, and HM model are combined to build the THM model, which is implemented in a GPU parallel multiphysics finite-discrete element software, namely MultiFracs. Finally, we use this THM model to study the hydraulic fracturing process of hot dry rock. The simulation results indicate that in addition to the primary fracture perpendicular to the direction of the minimum in situ stress, branching fractures along the direction of the minimum in situ stress are also produced during the hydraulic fracturing process. The proposed THM model can simulate heat and fluid transfer in fractured reservoirs, crack initiation, propagation, and intersection.